2021
DOI: 10.1177/09544089211015890
|View full text |Cite
|
Sign up to set email alerts
|

Semi-empirical modeling and optimization of process parameters on overcut during MFAPM-EDM of Al6061 alloy

Abstract: Magnetic field assisted powder mixed electrical discharge machining (MFAPM-EDM) process is a hybrid process machining process which improves the machining characteristics and stability of process using assistive magnetic field and dielectric admixed powder. In this article, study on overcut has been performed on MFAPM-EDM machined Aluminium 6061 alloy. Discharge current, powder concentration, pulse on duration, pulse off duration, and magnetic field strength as process parameters have been varied during experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Equations ( 3)- (5) give the correlation between the surface roughness, MRR and TWR with the process variables, respectively. The following sections discuss the regression equations, the analysis of variance, and the influence of the process parameters on the responses to evaluate the process performance.…”
Section: Regression Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations ( 3)- (5) give the correlation between the surface roughness, MRR and TWR with the process variables, respectively. The following sections discuss the regression equations, the analysis of variance, and the influence of the process parameters on the responses to evaluate the process performance.…”
Section: Regression Equationsmentioning
confidence: 99%
“…Studies have proved die-sink EDM to be technologically suitable for machining difficult-to-cut materials as it does not include work tool contact thus avoiding stresses, vibrations, and chatter as added advantages [4]. EDM uses spark erosion in which the electro-thermal energy of the electrical discharges in a dielectric fluid melts a part of the material from the work piece following the shape of the electrode [5]. However, a low Materials 2021, 14, 6192 2 of 16 MRR and a poor quality of the machined surface hinder the potential of this process.…”
Section: Introductionmentioning
confidence: 99%
“…These variables can be analyzed by MCDM methods. In the same way, multi-objective approaches also have difficulties achieving many goals at the same time [28]. Various approaches, such as metaheuristics, Pareto-based strategies, and multi-model independent direction, are used to address improvement challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the trials revealed that the discharge current is the most relevant parameter. The optimum process parameters for minimal overcut (OC) is 0.0801 mm was observed with a desirability index of 0.998 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%